The Effectiveness of the PanduHaid Application in Improving Independent Skills of Students with Mild Intellectual Disabilities During Menstruation - Sentia Andani Putri; Damri; Antoni Saputra; Rahmahtrisilvia (Jurnal Pedagogi dan Pembelajaran, 2025)
The limited independent ability of children with mild intellectual disabilities in managing menstrual hygiene presents a significant challenge in developing their self-reliance. The scarcity of adaptive learning media tailored to the cognitive characteristics of these children exacerbates this issue. This study aims to design, develop, and evaluate the effectiveness of the PanduHaid application as an interactive learning tool to enhance the independent menstrual hygiene management skills of children with mild intellectual disabilities. The research subjects consisted of several students with mild intellectual disabilities who were tested using a Research and Development (R&D) approach based on the ADDIE model. Data were collected through pretest-posttest instruments and expert validation, then analyzed quantitatively using the Wilcoxon Signed-Rank test. The results demonstrated that the PanduHaid application is highly valid and practical, with an Aiken’s V value > 0.90 and practicality score of 0.908, and effectively improved students' independent skills significantly (Z = -2.032, p = 0.042, r = 0.91). In conclusion, this application is effective and relevant as an inclusive learning media that supports the development of independence in children with mild intellectual disabilities. The implications of this study may serve as a reference for the development of adaptive technology-based learning media.